2017
DOI: 10.1111/imj.13382
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism management practices and knowledge of guidelines: a survey of Australian haematologists and respiratory physicians

Abstract: Background: Current international clinical practice guidelines do not adequately

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In addition, there is significant heterogeneity in the investigations and management of VTE at our centres, subject to physician preference and individual variability; hence, analysis of these aspects cannot be fully elucidated. A recent survey involving haematologists and respiratory physicians across Australia also demonstrated significant variability in VTE management, highlighting the need for national guidelines . Our ‘real‐world’ data provide a realistic overview of VTE in Melbourne compared to the typical clinical trial population, and could serve as the basis of comparison for future prospective observational studies in the era of DOAC.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, there is significant heterogeneity in the investigations and management of VTE at our centres, subject to physician preference and individual variability; hence, analysis of these aspects cannot be fully elucidated. A recent survey involving haematologists and respiratory physicians across Australia also demonstrated significant variability in VTE management, highlighting the need for national guidelines . Our ‘real‐world’ data provide a realistic overview of VTE in Melbourne compared to the typical clinical trial population, and could serve as the basis of comparison for future prospective observational studies in the era of DOAC.…”
Section: Discussionmentioning
confidence: 83%
“…A recent survey involving haematologists and respiratory physicians across Australia also demonstrated significant variability in VTE management, highlighting the need for national guidelines. 30 Our 'real-world' data provide a realistic overview of VTE in Melbourne compared to the typical clinical trial population, and could serve as the basis of comparison for future prospective observational studies in the era of DOAC.…”
Section: Discussionmentioning
confidence: 99%
“…Our study provided other important observations: First, there was infrequent documentation of PTP in ED records. Although this could have been performed, but not documented, a recent Australian survey showed that 38% of doctors rarely calculate and record it, suggesting this is an area for potential improvement . This is especially a concern if an AADD cut‐off is used since it is only validated if used in conjunction with PTP.…”
Section: Discussionmentioning
confidence: 99%
“…Although this could have been performed, but not documented, a recent Australian survey showed that 38% of doctors rarely calculate and record it, suggesting this is an area for potential improvement. 13 This is especially a concern if an AADD cut-off is used since it is only validated if used in conjunction with PTP. Second, only about one-third of patients proceeding to a CTPA had a D-dimer performed.…”
Section: Discussionmentioning
confidence: 99%
“…The condition has a high mortality despite treatment exceeding 2.7 per 100 VTE admissions . Despite several international clinical guideline publications, surveys of Australian practice show a lack of consistent approach to treatment and again this is likely to be replicated in other countries.…”
mentioning
confidence: 99%